Diversity, distribution and effects on cassava cultivars of Cassava Brown Streak Viruses in Malawi - Mbewe, W.; Kumar, P. Lava; Changadeya, W.; Ntawuruhunga, Pheneas; Legg, James P. (Wiley, 2015)
Cassava brown streak disease (CBSD) has emerged as a major threat to cassava ( Manihot esculenta ) in eastern and southern Africa. CBSD was first reported in Malawi in the 1950s, but little data on the distribution and epidemiology of the disease are available. A diagnostic survey was therefore conducted in Malawi to determine the distribution, incidence and diversity of viruses causing the disease, and to characterize its effects on local cassava cultivars. Diagnostic tests confirmed the presence of cas- sava brown streak viruses (CBSVs) in 90% of leaf samples from symp- tomatic plants. Average CBSD foliar severity was 2.5, although this varied significantly between districts. Both Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (genus Ipomovi- rus , family Potyviridae ) were detected from sampled plants. UCBSV was widespread, whereas CBSV was detected only in the two most northerly districts. The average abundance of the whitefly vector ( Bemisia tabaci ) was 0.4 per plant, a low value that was partly attributable to the fact that the survey was conducted during the cool part of the year known to be unfavourable for B. tabaci whiteflies. Spearman’s correlation analyses showed a positive correlation between CBSD foliar incidence and CBSD severity and between CBSD severity and CBSD stem incidence. Of the 31 cassava varieties encountered, 20 – 20 was most severely affected, whilst Mtutumusi was completely unaffected. Although data from this study do not indicate a significant CBSD deterioration in Malawi, strengthened management efforts are required to reduce the current impact of the disease.Cassava brown streak disease (CBSD) has emerged as a major threat to cassava ( Manihot esculenta ) in eastern and southern Africa. CBSD was first reported in Malawi in the 1950s, but little data on the distribution and epidemiology of the disease are available. A diagnostic survey was therefore conducted in Malawi to determine the distribution, incidence and diversity of viruses causing the disease, and to characterize its effects on local cassava cultivars. Diagnostic tests confirmed the presence of cas- sava brown streak viruses (CBSVs) in 90% of leaf samples from symp- tomatic plants. Average CBSD foliar severity was 2.5, although this varied significantly between districts. Both Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (genus Ipomovi- rus , family Potyviridae ) were detected from sampled plants. UCBSV was widespread, whereas CBSV was detected only in the two most northerly districts. The average abundance of the whitefly vector ( Bemisia tabaci ) was 0.4 per plant, a low value that was partly attributable to the fact that the survey was conducted during the cool part of the year known to be unfavourable for B. tabaci whiteflies. Spearman’s correlation analyses showed a positive correlation between CBSD foliar incidence and CBSD severity and between CBSD severity and CBSD stem incidence. Of the 31 cassava varieties encountered, 20 – 20 was most severely affected, whilst Mtutumusi was completely unaffected. Although data from this study do not indicate a significant CBSD deterioration in Malawi, strengthened management efforts are required to reduce the current impact of the disease.Cassava brown streak disease (CBSD) has emerged as a major threat to cassava ( Manihot esculenta ) in eastern and southern Africa. CBSD was first reported in Malawi in the 1950s, but little data on the distribution and epidemiology of the disease are available. A diagnostic survey was therefore conducted in Malawi to determine the distribution, incidence and diversity of viruses causing the disease, and to characterize its effects on local cassava cultivars. Diagnostic tests confirmed the presence of cas- sava brown streak viruses (CBSVs) in 90% of leaf samples from symp- tomatic plants. Average CBSD foliar severity was 2.5, although this varied significantly between districts. Both Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (genus Ipomovi- rus , family Potyviridae ) were detected from sampled plants. UCBSV was widespread, whereas CBSV was detected only in the two most northerly districts. The average abundance of the whitefly vector ( Bemisia tabaci ) was 0.4 per plant, a low value that was partly attributable to the fact that the survey was conducted during the cool part of the year known to be unfavourable for B. tabaci whiteflies. Spearman’s correlation analyses showed a positive correlation between CBSD foliar incidence and CBSD severity and between CBSD severity and CBSD stem incidence. Of the 31 cassava varieties encountered, 20 – 20 was most severely affected, whilst Mtutumusi was completely unaffected. Although data from this study do not indicate a significant CBSD deterioration in Malawi, strengthened management efforts are required to reduce the current impact of the disease.